Unemployment in Ireland : A Survey of Features and Causes - Santaella, Julio (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1995)
This paper examines the problem of unemployment in Ireland. A brief description of the main distinctive features of the structure of Irish unemployment is presented. Based on up to date literature, the possible causes behind unemployment are reviewed. Empirical studies that have quantified the contributions of different determinants to the increase in Irish unemployment are also surveyed. The paper concludes with some policy suggestions.